Bone marrow transplantation/non-bone marrow transplantation gap: to what extent does it exist in the Egyptian children with acquired aplastic anemia? Retrospective descriptive study - Mohamed Abdallah Abd El Megied; Rasha Abdel-Raouf; Howida Ahmed Ali (SpringerOpen, 2023)
Abstract Background Bone marrow transplantation (BMT) is not always feasible in resources-limited countries for treatment of acquired aplastic anemia (AA); accordingly, an alternative and acceptable non-BMT is required to avoid missing many cases who are liable to die while waiting for BMT. The aim of this study was to determine the extent of the gap between BMT and non-BMT in Egypt. The resolution and survival outcomes of BMT versus non-BMT therapy (isolated IST, combined IST & Eltrombopag (EPAG) (double therapy) and combined IST and EPAG and anti-thymocyte globulin (ATG) (triple therapy)) were evaluated. Methods Medical records were reviewed for epidemiological and clinical data, as well as response to BMT and non-BMT used. Sixty patients with acquired AA were involved. BMT was performed in 18 patients, while non-BMT was performed in 42 patients. Results Resolution occurred in 13/18 (72.2%) patients treated with BMT, 5/14 (35.7%) isolated IST, 10/12 (83.3%) combined IST-EPAG, and 12/16 (75%) triple ATG-IST-EPAG with an overall resolution occurring in 27/42 (64.2%). The percentage of survivors in those treated with BMT was 72.2%, isolated IST 5/14 (35.7%), double therapy 10/12 (83.3%), and triple therapy 10/16 (62.5%) with an overall survivor occurring in 25/42 (59.5%). Despite the lack of a statistically significant correlation, it was found that patients who received BMT had 1.769 times higher survival rates than those who received non-BMT. Conclusion In Egypt, BMT is the ideal therapy for acquired AA with acceptable results for non-BMT regarding resolution and survival. Double therapy is the best modality of non-BMT regarding resolution and survival. Accordingly, it is recommended to be initiated in case of unavailable matched donor.